2006
DOI: 10.1093/ndt/gfl606
|View full text |Cite
|
Sign up to set email alerts
|

Sodium citrate 4% locking solution for central venous dialysis catheters--an effective, more cost-efficient alternative to heparin

Abstract: The pharmaco-economic benefits of sodium citrate 4% are well supported by this analysis. Furthermore, citrate offers several clinical advantages over concentrated heparin: citrate lock avoids heparin-associated bleeding complications, improves reliability of INR assays and provides an effective alternative for patients with suspected or confirmed heparin-induced thrombocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 21 publications
4
102
0
3
Order By: Relevance
“…The largest experience reported is that from Grudzinski et al (42) during a conversion study from heparin 10,000 U/ml to 4% citrate locks. The rate of flow-related catheter exchange, tPA use, and bacteremia did not differ in the year of heparin locks compared with the subsequent year of citrate locks with over 30,000 catheter days at risk in each period.…”
Section: Maintaining Patency With Catheter Locking Solutions Between mentioning
confidence: 99%
“…The largest experience reported is that from Grudzinski et al (42) during a conversion study from heparin 10,000 U/ml to 4% citrate locks. The rate of flow-related catheter exchange, tPA use, and bacteremia did not differ in the year of heparin locks compared with the subsequent year of citrate locks with over 30,000 catheter days at risk in each period.…”
Section: Maintaining Patency With Catheter Locking Solutions Between mentioning
confidence: 99%
“…The FDA also advised that a 4% citrate solution should be used as an alternative [62]. Recently, it has been shown that a 4% citrate solution is effective in maintaining catheter patency [63,64] and has not been demonstrated to induce systemic anticoagulation or hypocalcemia. The same study found that the incidence of CRB before versus after switching from heparin to citrate 4% was similar.…”
Section: B Preventing Contamination Of the Catheter Hubmentioning
confidence: 99%
“…8,9 Given these adverse outcomes and high costs, further research on strategies to optimize the use of hemodialysis catheters is required, particularly with regard to preventing the most common adverse catheter outcomes of malfunction (i.e., inability to initiate or continue dialysis because of to inadequate bloodflow, often the result of catheter thrombosis) and bacteremia. 5,6 Heparin has traditionally been used as an intradialytic catheter locking solution, although other agents are now used, including citrate 10,11 and recombinant tissue plasminogen activator (rt-PA). 12 Intradialytic locking with a thrombolytic agent has many appealing features.…”
mentioning
confidence: 99%